Altered levels of shorter vs long-chain omega-3 fatty acids in commercial diets for market-sized Atlantic salmon reared in seawater – Effects on fatty acid composition, metabolism and product quality - Mock, Thomas S; Francis, David S; Jago, Matthew K; Glencross, Brett D; Smullen, Richard P; Keast, Russell S J; Turchini, Giovanni M (Aquaculture, 2019)
There is a growing trend of ‘replacing’ long-chain omega-3 polyunsaturated fatty acid (n-3 LC PUFA) rich oils with C18 shorter-chain omega-3 polyunsaturated fatty acid rich oils in Atlantic salmon aquafeed formulations. n-3 LC PUFA, including 20:5n-3 and 22:6n-3, play contrasting physiological roles and are metabolised differently in comparison to C18 PUFA. Accordingly, the present study recorded the effect of replacing n-3 LC PUFA rich dietary fish oil with C18 n-3 PUFA rich camelina oil at two inclusion levels in commercial-like diets fed to market-sized Atlantic salmon. This assessment was achieved by an analysis of industry relevant production parameters including growth performance, fatty acid composition and metabolism, nutrient digestibility and consumer acceptance (liking and attribute analysis of fillet). The trial was conducted over the final 150 days of an on-farm grow-out period in seawater. The dietary replacement of n-3 LC PUFA with C18 n-3 PUFA resulted in a significant decrease in fillet n-3 LC PUFA and a poorer growth performance. However, in the absence of fish oil, the inclusion of camelina oil at high levels (40%) contributed to an improved n-6/n-3 ratio and partially ameliorated low dietary n-3 LC PUFA by providing added substrate for endogenous n-3 LC PUFA synthesis in comparison to a 20% camelina oil inclusion. Furthermore, consumer acceptance of Atlantic salmon was unaffected by the dietary addition of camelina oil.